2013
DOI: 10.1016/j.matdes.2013.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkages and warpage in the processability of wood-filled polypropylene composite thin-walled parts formed by injection molding

Abstract: a b s t r a c tReducing volumetric shrinkages and warpage during the injection molding process is a challenging problem in the production of molded thin-walled parts. In this study, the injection molding of shallow, thinwalled parts (thickness 0.7 mm), composed of lignocellulosic polymer composites (polypropylene (PP) + 50 wt% wood), was simulated. The volumetric shrinkages and warpage in the thin-walled parts were evaluated under different process conditions, with varying post-filling parameters, such as mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 28 publications
3
37
0
1
Order By: Relevance
“…This trend also agreed by Mehat et al [14] who indicated that shrinkage significantly reduced by increasing the packing pressure. On the other hand, the cooling time was agreed by Azaman et al [13] to have less effect on the shrinkage on the moulded parts. The regression model from Table 5 shows the relationship between the shrinkage and all input parameters which are mould temperature (A), melt temperature (B), packing pressure (C) and packing time (D) was established by Design Expert software and represented as Eq.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This trend also agreed by Mehat et al [14] who indicated that shrinkage significantly reduced by increasing the packing pressure. On the other hand, the cooling time was agreed by Azaman et al [13] to have less effect on the shrinkage on the moulded parts. The regression model from Table 5 shows the relationship between the shrinkage and all input parameters which are mould temperature (A), melt temperature (B), packing pressure (C) and packing time (D) was established by Design Expert software and represented as Eq.…”
Section: Resultsmentioning
confidence: 90%
“…This result is in line with Altan [12] who found that the packing pressure is the most significant factor for shrinkage and followed by melt temperature. Besides, Azaman et al [13] also reported that packing pressure has a significant effect on shrinkage where the higher packing pressure resulted a lower shrinkage and vice versa. This trend also agreed by Mehat et al [14] who indicated that shrinkage significantly reduced by increasing the packing pressure.…”
Section: Resultsmentioning
confidence: 98%
“…by adding varieties of fine fillers [1][2][3][4]. During the injection molding process, different parameters setting of injection molding process will have direct and import effect on the quality of the plastic product [5][6][7][8][9].…”
Section: ������������ ������������mentioning
confidence: 99%
“…Nowadays, many sophisticated software packages are available, which can simulate, analyze, and generate injection molding data based on selected input and output parameters. Numerous works using such software packages have been reported, e.g., Moldflow ® in the fabrication of window frames using rice husk filled polyethylene composites [94], Moldflow ® combined with Autodesk Inventor r for modeling and simulating shallow and flat thin walled molds of a polymer composite [5,6], Moldflow ® to determine significant parameters affecting the shrinkage of molded components [69], Moldflow ® to study material distribution and melt flow behaviour in sandwich molding process [92], Moldflow ® combined with the Taguchi method to determine the optimal design parameters by minimizing the warpage of gas assisted molding components [14], and Moldflow ® integrated with the Taguchi method to study the effects of processing parameters on the molding of ultra-thin wall polymer components [102]. Apart from that, Moldflow ® was applied to some other similar works also, e.g., simulation of feedstock properties for powder injection molding of thermal management devices [86], feedstock properties and injection molding simulations of bimodal mixtures [49], measurements of powder-polymer mixture properties and their use in powder injection molding simulations [48], powder injection molding of ceramic engine components for transportation [61], effects of nanoparticle addition on processing of alloys [85], powder injection molding of parts for UAV engine components [74], etc.…”
Section: Hard Computing Techniquesmentioning
confidence: 99%